Cognitive training as a potential treatment for overweight and obesity: A critical review of the evidence. (1st May 2018) - Jones, Andrew; Hardman, Charlotte A.; Lawrence, Natalia; Field, Matt
Abstract: The aim of this review is to critically evaluate the effectiveness and candidate mechanisms of action of psychological interventions which aim to either (a) improve the capacity for self-regulatory, reflective processes or (b) reduce the impact of automatic appetitive processes, in an attempt to influence food intake and associated weight-gain. Our aim was to examine three important issues regarding each type of intervention: i) whether the intervention influenced behaviour in the laboratory, ii) whether the intervention influenced behaviour and/or body mass index in the real world, and iii) whether the proposed mechanism of action was supported by evidence. We systematically searched three commonly used databases and identified 32 articles which were relevant to at least one of these issues. The majority of studies attempted to manipulate food intake in the laboratory using associative learning paradigms, in normal-weight female participants. Most of the laboratory studies demonstrated the predicted effects of interventions on behaviour in the laboratory, but studies that attempted to translate these interventions outside of the laboratory yielded more mixed findings. The hypothesised mechanisms of action received inconsistent support across studies. We identified several limitations which may complicate interpretation of findings in this area, including heterogeneity of study methods, small sample sizes, and absence of adequate control groups. We provide recommendations for future studies that aim to develop and evaluate these promising interventions for the reduction of overweight and obesity.